1993
DOI: 10.1063/1.1144462
|View full text |Cite
|
Sign up to set email alerts
|

Digital signal processor control of scanned probe microscopes

Abstract: Digital signal processors have made it possible to control scanned probe microscopes using straightforward software emulations of analog circuits. Using a system consisting of a commerciaIly available digital signal processor board interfaced to analog I/O, we have developed algorithms for self-optimizing feedback, raster generation (with hysteresis correction, sample tilt compensation, and scan rotation), lock-in detection, and automatic tip-sample approach. We also discuss an instruction parser that takes ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Recent studies have shown that elastic properties of cells can be detected with the AFM (Hoh and Schoenenberger, 1994). Imaging of elastic properties with the AFM is possible using force modulation (Radmacher et al, 1993;Baselt et al, 1993), which has been applied to platelets (Radmacher et al, 1992) and magnetotactic bacteria . Quantitative analysis of the elastic or other sample properties can be obtained with the AFM by taking force curves, as pointed out earlier (Burnham and Colton, 1989;Weisenhom et al, 1989Weisenhom et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that elastic properties of cells can be detected with the AFM (Hoh and Schoenenberger, 1994). Imaging of elastic properties with the AFM is possible using force modulation (Radmacher et al, 1993;Baselt et al, 1993), which has been applied to platelets (Radmacher et al, 1992) and magnetotactic bacteria . Quantitative analysis of the elastic or other sample properties can be obtained with the AFM by taking force curves, as pointed out earlier (Burnham and Colton, 1989;Weisenhom et al, 1989Weisenhom et al, , 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously the original analog control circuits (Binnig et al , 1982;Munoz et al , 1998) fail to meet this requirement. The digital control methods popular nowadays are usually composed of a computer and digital circuits such as a digital signal processor (DSP) (Wong and Welland 1993;Baselt et al , 1993;Heuel et al , 1994;Barchesi et al , 1997;Scheuring et al , 1998;Boudreau et al , 2002). The digital circuits perform the core control routine which is to a large extent fixed by the original designer, and the modifications require professional knowledge and abundant experience.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This system uses an optical lever detection scheme to monitor the cantilever displacement. In order to determine the frequency characteristics of the cantilever motion, the output of the photodiode preamplifier was connected directly to a HP spectrum analyzer.…”
Section: Methodsmentioning
confidence: 99%